Ultrasound Imaging of Normal Displacement of the Extensor Carpi Ulnaris Tendon Within the Ulnar Groove in 12 Forearm-Wrist Positions - Lee, Kenneth S; Ablove, Robert H; Singh, Steven; De Smet, Arthur A; Haaland, Benjamin; Fine, Jason P (American journal of roentgenology (1976), 2009)
Instability of the extensor carpi ulnaris (ECU) tendon can be a difficult clinical diagnosis because of normal changes in tendon position during wrist motion. Our goal was to determine the normal variation of ECU tendon displacement in 12 forearm-wrist positions. Ultrasound imaging of the ECU tendons of 40 symptom-free wrists of healthy volunteers (13 women, seven men; mean age, 22.3 years; range, 20-25 years) was performed. Each ECU tendon was examined in 12 positions: four wrist positions (ulnar deviation, radial deviation, flexion, and extension) in each of three forearm positions (pronation, supination, and neutral). ECU tendon displacement in the right hand was not significantly different from that in the left, and displacement in men did not differ significantly from that in women. There was a small but significant difference between displacement in the dominant and that in the nondominant hand (p < 0.02). Mean ECU tendon displacement was greatest in the supinated forearm position (p < 0.001) followed by the neutral position (p < 0.001) and was least in the pronated position (p < 0.001). Both ulnar deviation (p < 0.001) and flexion (p < 0.002) were associated with greater ECU tendon displacement than were radial deviation (p < 0.001) and extension (p < 0.002). Maximum percentage displacement volar to the ulnar border of the groove was 50% in flexed supination and ulnar deviation. The maximum displaced distance volar to the ulnar border of the groove was 5 mm. Sonographic evaluation of the ECU tendon is simple and practical. Knowledge of normal ECU displacement relative to the ulnar groove may help in evaluation of ulnar-sided wrist pain.